2020
DOI: 10.1038/s41598-020-80123-5
|View full text |Cite
|
Sign up to set email alerts
|

Root-associated entomopathogenic fungi manipulate host plants to attract herbivorous insects

Abstract: Root-associated entomopathogenic fungi (R-AEF) indirectly influence herbivorous insect performance. However, host plant-R-AEF interactions and R-AEF as biological control agents have been studied independently and without much attention to the potential synergy between these functional traits. In this study, we evaluated behavioral responses of cabbage root flies [Delia radicum L. (Diptera: Anthomyiidae)] to a host plant (white cabbage cabbage Brassica oleracea var. capitata f. alba cv. Castello L.) with and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 55 publications
0
23
0
Order By: Relevance
“…The species M. brunneum is less characterized for its effects on herbivory, but recently, has been shown to induce resistance against pests and pathogens [ 78 ]. Furthermore, isolate KVL 16–36 has been shown to alter the plant phenotype [ 79 ]. Both fungal isolates are obtained from commercial biocontrol products, which make them available for use in plant production systems in several countries.…”
Section: Methodsmentioning
confidence: 99%
“…The species M. brunneum is less characterized for its effects on herbivory, but recently, has been shown to induce resistance against pests and pathogens [ 78 ]. Furthermore, isolate KVL 16–36 has been shown to alter the plant phenotype [ 79 ]. Both fungal isolates are obtained from commercial biocontrol products, which make them available for use in plant production systems in several countries.…”
Section: Methodsmentioning
confidence: 99%
“…The fungal-induced change in leaf reflectance may have altered visual cues used by the cabbage root flies in their host plant selection. This provides first evidence for the hypothesis that R-AEF manipulate the suitability of their host plant to attract herbivorous insects …”
Section: Challengesmentioning
confidence: 67%
“…Another case study showed sensory integration in the cabbage root fly Delia radicum (Diptera: Anthomyiidae) during the host location and in the interaction with a root-associated entomopathogenic fungi (R-AEF) . It is known that R-AEF indirectly influence herbivorous insect performance .…”
Section: Challengesmentioning
confidence: 99%
“…For studies related to endophyte-induced secondary compounds, phytohormones, and enzymes, several molecular analyses are commonly being used. The most common technologies used include liquid chromatography-mass spectrometry (LC-MS-MS; Wang et al, 2020 ), gas chromatography-mass spectrometry (GC-MS/MS; Elbanhawy et al, 2019 ), high pressure liquid chromatography-tandem mass spectrometry (HPLC-MS/MS), ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS; Cotes et al, 2020 ), nuclear magnetic resonance spectroscopy (NMR), headspace solid-phase microextraction (HS-SPME), Fourier transform infrared spectroscopy (FTIR), and proteomics ( Al-Ani et al, 2021 ).…”
Section: Overview Of the Research Advances In The Last Few Decades And Insights For Next-generation Sustainable Agriculturementioning
confidence: 99%
“…Fungal endophytes are believed to serve as bodyguards for their host plants against primary herbivore pests (Vidal and Jaber, 2015;Jaber and Ownley, 2018). Under moderate to high levels of herbivore attack, plants colonized with endophytic fungi can generally outperform endophyte-free plants (Clay, 1997).…”
Section: Entomopathogenic Fungi Mediating Plant Defense Against Insect Pestsmentioning
confidence: 99%